Staff Motivation in Special Libraries in Ghana - Owusu-Acheaw, M. (Ghana Library Journal, 2003)
The study sought to examine why many library workers seem to drift towards special libraries rather than to other types of libraries. It also aimed at finding out whether the seeming drift towards special libraries was caused by the fact that special libraries motivated their staff better than other library organizations and how motivation affected productivity. The use of questionnaire, observation and personal interviews with the management staff and the library staff of the organization whose special libraries were studied made it possible to draw certain conclusions. The questionnaire was designed to check and double-check the responses elicited from the two sets of populations which were involved in the data collection. The interview segment was also to probe further for information to clarify certain issues and confirm perceptions and attitudes that came out at some points in the administration of the questionnaire. The result was that responses were wholly confirmed or wholly denied by the subjects thereby making it possible to authenticate conclusions to be made from the survey.